Edukasi Kewaspadaan Kanker Payudara untuk Siswi SMPN 24 Kota Padang dengan Menggunakan Metode Virtual Reality - Boby Febri Krisdianto; Tiurmaida Simandalahi; Sidaria Sidaria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Early detection of cancer begins with increasing public awareness about abnormalities in the breast through the breast self-examination (BSE) program. The interest of young women in seeking information about breast cancer is still so low that the purpose of this activity is to provide health education on breast cancer awareness and demonstrations of doing BSE to students of SMPN 24 Padang City. The health education method is Virtual Reality Technology and BSE demonstration using mannequins. Participants were given a pretest and posttest quiz to know the value of breast cancer awareness. This activity was held on Saturday, August 13, 2022, at SMP 24 Padang. The result shows increased breast cancer awareness among SMPN 24 Padang students. It is hoped that Virtual Reality (VR) technology will be used more in health education because it is one of the solutions that can help educators provide more fun learning.